Comparison of Bright Band Radar from GPM and MRR Observation in West Sumatera - Ramadhan, Ravidho; Marzuki, Marzuki; Vonnisa, Mutya; Harmadi, Harmadi; Hashiguchi, Hiroyuki; Shimomai, Toyoshi (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
AbstractThe Bright band (BB) measurement from NS scan on Global Precipitation Measurement (GPM) had been compared with Micro Rain Radar (MRR) which is installed in Kototabang, West Sumatera (0.23o S; 100.32oE; 865 m above sea level). The GPM data were collected from December 2014 to June 2018 and compared with MRR observation from January 2012 to August 2016. The BB values from these instruments were also compared with the values recommended by the International Telecommunication Union Recommendation (ITU-R) P.839. The BB from GPM and MRR shown slightly diurnal and seasonal variations. BB observations from GPM and MRR show good agreement with slightly difference in diurnal and seasonal variations. BB observations are more similar when the intensity of solar radiation is lower, ie at night (18.00-24.00 LT) until dawn (00.00-06.00 LT). Furthermore, MRR determined a slight bimodal pattern in the seasonal variation while GPM did not, it cause variation in observation of both instrument quite significant in seasonal variation. The largest different from the seasonal variation was observed in the summer season (Juni-August(JJA)). Moreover the measurement of the mean BB is still below the Freezing Height Level (FHL) value from ITU-R model, the measurement of both instruments obtained a high number than FHL considerably (>36 %). It showed the constant value for FHL in West Sumatera that would cause the attenuation estimation of microwaves to be less accurate.